Sustainability Study Of Small And Medium Industries Based On Local Wisdom In Denpasar City - I Gede Yudiantara; I Ketut Sudibia; Ni Nyoman Yuliarmi (Universitas Udayana, 2024)
Small and Medium Industries are the foundation of the people's economy which plays arole in channeling the creative and innovative spirit into superior products and localwisdom. This research aims to analyze the sustainability study of local wisdom-basedSMEs in Denpasar City. This research uses an associative quantitative approach withprimary data from 144 respondents. Using the purposive sampling method and thedata analysis technique used in this research is SEM Partial Least Square. The researchresults show that social capital, entrepreneurial orientation and local wisdom have apositive and significant effect on business performance, while the role of governmentdoes not have a significant effect on business performance. The role of government,social capital, entrepreneurial orientation, and business performance have a positiveand significant effect on the sustainability of SMEs. Local wisdom moderates theinfluence of social capital on SME business performance. Meanwhile, social capital andentrepreneurial orientation have an indirect effect on sustainability through businessperformance, while the role of government has no indirect effect on sustainabilitythrough SME business performance.